Castellated Abbeys, Fortified Enclaves: Immunity and Sovereignty in Edgar Allan Poe's 'Masque of the Red Death' and Contemporary Brazil. Issue 1 (31st March 2023) - Baker, Emily
This essay uses elements of Roberto Esposito's immunitary paradigm to shed light on Edgar Allan Poe's "Masque of the Red Death" and, in parallel, to think through social and spatial stratification in contemporary Brazil. I argue that racial anxiety is at the heart of both Poe's story and the particular spatial tendency in Brazil's cities of elites to live in "fortified enclaves" (Caldeira), comparable in many ways to the "castellated abbey" of Poe's story. In examining the effects of the "Red Death", or Covid-19 in Brazil under Jair Bolsonaro's government, I observe that Bolsonaro's status as a democratically elected official (unlike Prince Prospero) has forced him to give certain concessions to the population, in the form of aid payments, that maintain his power. However, I demonstrate that this is not incompatible with an active thanatopolitical strategy, which encourages the most marginalized in society to expose themselves to the virus (and thus to death). Finally, I turn to Jean-Luc Nancy's short essay "Communavirus", which outlines the ethical potential of community-in-isolation but which does not take into account places such as the favelas of Brazil, where isolation is often not practically or materially possible.